Studi slavistici tra linguistica, dialettologia e filologia - Benacchio, Rosanna (Biblioteca di Studi Slavistici, 2022)
The volume contains a selection of some of the most representative works from Rosanna Benacchio's extensive scientific production. It is divided into three parts, the first one being dedicated to the category of verbal aspect in the Slavic languages. The second part deals with Slavic minority varieties spoken in Italy, in particular the Slovene dialects of Friuli and Molise Slavic. The third part focuses on three linguistic phenomena that are analysed from a diachronic perspective: the referential usage of the personal pronoun Vy in the Petrine era; the use of clitic pronouns in the Slavic languages; the formation of the definite article in the Slovene area based on the evidence of the Resian Catechism of the 18th century.